Hypoxia and Non-alcoholic Fatty Liver Disease - Isaza, Stephania C.; del Pozo-Maroto, Elvira; Domínguez-Alcón, Lucía; Elbouayadi, Liliam; González-Rodríguez, Águeda; García-Monzón, Carmelo (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) is currently the commonest chronic liver disease worldwide and comprises varied grades of intrahepatic lipid accumulation, inflammation, ballooning and fibrosis; the most severe cases result in cirrhosis and liver failure. There is extensive clinical and experimental evidence indicating that chronic intermittent hypoxia, featuring a respiratory disorder of growing prevalence worldwide termed obstructive sleep apnea, could contribute to the progression of NAFLD from simple steatosis, also termed non-alcoholic fatty liver or hepatosteatosis, to non-alcoholic steatohepatitis; however, molecular mechanisms by which hypoxia might contribute to hepatosteatosis setup and progression still remain to be fully elucidated. In this review, we have prepared an overview about the link between hypoxia and lipid accumulation within the liver, focusing on the impact of hypoxia on the molecular mechanisms underlying hepatosteatosis onset.